FACTORS THAT INFLUENCE WOMEN STAFF OF UNIVERSITY UTARA MALAYSIA TO PRACTICE RASULULLAH'S S.A.W. METHODOLOGY IN CHILDREN EDUCATION - Syed Sultan Bee (Journal of Islamic, Social, Economics and Development, 2018)
Parents are fully responsible to educate their children using the right and proper way.This is to save them from falling into social problems and moral decline which are increasingamong teenagers lately. The increasing of social problems indirectly shows that there areimperfections and mistakes made by parents today in educating their children. Hence, parentsneed to be given the awareness on the importance of educating children by practicing thecorrect methodology, namely Rasulullah's s.a.w. methodology as the solution to this problem.Consequently, a quantitative study was conducted to investigate the factors that influencewomen staff of University Utara Malaysia (UUM) to practice Rasulullah's s.a.w. methodologyin children education. This study involves a total of 306 respondents consisting theadministrative and academic staff. Questionnaires were used to collect data while StatisticalPackages for Social Sciences (SPSS) version 22.0 was used to analyze the collected data. Thefindings of the study show that majority among the women staff of UUM agreed that family,environment, education, mass media and self-awareness factors have influenced them toeducate their children by practicing Rasulullah’s s.a.w. education methodology. The outcomeof this study is expected to give parents awareness to practice Rasulullah’s s.a.w. methodologyin educating children in order to decrease social problems among younger generation in thiscountry, besides producing more Muslim individuals with good moral and personality.